MODAL SOSIAL DALAM PEMERINTAHAN DAERAH: ANALISIS PERAN MODAL SOSIAL DALAM PENYELENGGARAAN SEMARANG NIGHT CARNIVAL - Willy - Valentino; Kushandajani - -; puji - Astuti (Journal of Politic and Government Studies, 2023)
Currently, local festivals have become the government programs of many local governments in Indonesia. Several excellent local festivals show that social capital is a fundamental resource in the implementation process of it. Semarang has been presenting Semarang Night Carnival as a government program aimed to appreciate arts and at the same time promote the City of Semarang itself since 2011. However, the recognition that Semarang Night Carnival received is not as good as the leading festivals from other regions. This research aims to identify and analyze the role of social capital in Semarang Night Carnival. This is a descriptive qulitative research, and using interviews and observations as the data collecting techniques. The results showed that the role of social capital in Semarang Night Carnival was not significant. This can be seen from the social capital indicators, bonding and bridging, that are not going well as the supporting source for this festival sustainability. However, other indicator in the form of linking in this festival has the potential to maintain the existence of this festival. Even though the role of social capital in this festival is not optimal yet, this government program shows that social capital has the potential to be a supporting source of good local governance through the efforts of the City of Semarang’s Government to collaborate with community while being supported by the norm of reciprocity